Physical-chemical characterization of biomass samples for application iin pyrolysis process - Braz, Carlos Eduardo Mendes [UNESP]; Crnkovic, Paula Cristina Garcia Manoel [UNESP] (My University, 2014)
The use of lignocellulosic biomass as an energy source has considerably increased. Due to the diverse natures of biomass materials, their properties widely range and exhibit different behaviors in thermal processes. The most important properties that provide information about a fuel are heating values, ash composition, proximate (determination of moisture, ash, volatile and fixed carbon content), and ultimate analysis (C, H, N, S and O composition). Moreover, the kinetic study of the thermal behavior of a fuel can be useful for the understanding of the complex decomposition process of each material. This study focuses on the physical-chemical characterization of six lignocellulosic biomasses, namely coffee husk, tucumã seed, sugar cane bagasse, peanut shell, rice husk and pine sawdust, widely available in Brazil. A thermogravimetric analyzer was used to study their decomposition behavior in a pyrolytic environment. Non-isothermal thermogravimetric data were used and the application of a model-free isoconversional method enabled the evaluation of the activation energy (Ea) of the biofuels. The curves also show that the behavior during thermal decomposition varies from one biomass to another and these differences imply the importance of a comprehensive characterization study of fuels for the development and optimization of reactors. The knowledge on biomass properties enables the prediction of environmental impacts and technical aspects related to thermal processes. Therefore, thermal decomposition behavior is a consequence of the feedstock physical-chemical characteristic, which also provides valuable information regarding features of the complex reactions that occur throughout the pyrolysis of the biomass.